Advances in planning and management of watersheds and wetlands in Ea stern and Southern Africa - FitzGibbon, John E.; The University of Guelph. Environmental Capacity Enhancement Project . (Harare : Weaver Press, 1999)
Copyright: The University of Guelph, Canada.
Keywords: Wetlands -- Africa, Eastern; Wetlands -- Africa, Southern; Watershed management -- Africa, Eastern; Watershed management -- Africa, Southern